ANALISIS KINERJA KEUANGAN, UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING - Apriasih; Arifin Siagian; Noviarti (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2023)
This research aims to examine and provide empirical evidence on the effect of profitability, company size, and leverage on company value with dividend policy as an intervening variable in the food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange (BEI). The population in this research is food and beverage sector companies listed on the Indonesia Stock Exchange. The sampling technique used in this research is purposive sampling with a total of 10 companies. The data analysis method used in this research is using Partial Least Square (SmartPLS) version 3.0. The results of the research show that profitability, company size, and leverage do not have a direct effect on dividend policy. Profitability and dividend policy have a direct effect on company value. Against company size and leverage do not have a direct effect on company value. And for profitability, company size, and leverage do not have an effect on company value through dividend policy as an intervening variable.